درجة توافق القيم الشخصية والقيم التنظيمية لدى مديري مدارس التعليم الأساسي بمحافظتي شمال وجنوب الشرقية في سلطنة عمان - المعايطة، عبدالعزيز عطا الله; الراجحي، سليمان بن عامر (كلية الإمارات للعلوم التربوية, 2017)
The study aimed to identify personal values and organizational values with Basic education schools principals in the provinces of South and North of al sharqia Region in Oman. In order to achieve the goal, I designed a questionnaire Consisting of 52 paragraphs. After making sure of its validity and reliability, it is applied to 178 principals in the academic year of 2014/2015.To answer the study questions I extracted Average Account, standard deviations, Analysis of variance and posteriori Comparisons. This study found set of results, the Most notably one is that, the Agree personal values and organizational values degree in south and north of Alsharqia region basic schools principals is low. Also the results indicate that there were no statistical differences in semantics (0,05,a). Due to the impact of variable gender and experience. While there were statistically significant differences (0,05,a) Due to the impact of variable Qualification. The differences were in favor of Graduate Studies, Also There is a positive correlation statistically significant relationship between personal and organizational values. In light of the results, the researchers recommend providing training courses for principals in the self-development field, to enable them to personal and organizational values Control and have a positive influence on the educational field. Also, benefit from teachers views in school life and take their views into account.
هدفت الدراسة إلى التعرف على درجة توافق القيم الشخصية والقيم التنظيمية لدى مديري مدارس التعليم الأساسي بمحافظتي شمال وجنوب الشرقية في سلطنة عمان ومن أجل تحقيق الهدف صممت استبانة مكونة من (52) فقرة، وبعد التأكد من دلالات صدقها وثباتها طبقت على (178) مديرا ومديرة في العام الدراسي 2014/2015م. وللإجابة على أسئلة الدراسة استخرجت المتوسطات الحسابية، والانحرافات المعيارية وتحليل التباين والمقارنات البعدية وقد توصلت الدراسة إلى مجموعة من النتائج كان من أبرزها أن درجة توافق القيم الشخصية والقيم التنظيمية لدى مديري مدارس التعليم الأساسي بمحافظتي شمال وجنوب الشرقية في سلطنة عمان متدنية، كما أشارت النتائج إلى عدم وجود فروق ذات دلاله إحصائية (0,05,a) تعزى لأثر متغير النوع الاجتماعي والخبرة، بينما كانت هناك فروق ذات دلاله إحصائية (0,05,a) تعزى لأثر متغير المؤهل العلمي وجاءت الفروق لصالح الدراسات العليا وأيضا توجد علاقة ارتباطيه إيجابية داله إحصائيا بين القيم الشخصية والقيم التنظيمية. وفي ضوء النتائج يوصي الباحثان بتقديم دورات تدريبية لمديري المدارس في مجال تطوير الذات لتمكينهم من التحكم بالقيم الشخصية والتنظيمية بحيث يكون تأثيرها إيجابي على الحقل التربوي والاستفادة من أراء المعلمين في الحياة المدرسة وأخذ ارائهم بعين الاعتبار.
Keywords: سلطنة عمان -- التعليم الأساسي -- مديرو المدارس -- السلوك التنظيمي